A multispecies approach for understanding neuroimmune mechanisms of stress. Issue 1 (31st March 2017) - Deak, Terrence; Kudinova, Anastacia; Lovelock, Dennis F.; Gibb, Brandon E.; Hennessy, Michael B.
Abstract : The relationship between stress challenges and adverse health outcomes, particularly for the development of affective disorders, is now well established. The highly conserved neuroimmune mechanisms through which responses to stressors are transcribed into effects on males and females have recently garnered much attention from researchers and clinicians alike. The use of animal models, from mice to guinea pigs to primates, has greatly increased our understanding of these mechanisms on the molecular, cellular, and behavioral levels, and research in humans has identified particular brain regions and connections of interest, as well as associations between stress-induced inflammation and psychiatric disorders. This review brings together findings from multiple species in order to better understand how the mechanisms of the neuroimmune response to stress contribute to stress-related psychopathologies, such as major depressive disorder, schizophrenia, and bipolar disorder.